2018
DOI: 10.1016/j.foodres.2018.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Atlantic salmon (Salmo salar) co-product-derived protein hydrolysates: A source of antidiabetic peptides

Abstract: Large quantities of low-value protein rich co-products, such as salmon skin and trimmings, are generated annually. These co-products can be upgraded to high-value functional ingredients. The aim of this study was to assess the antidiabetic potential of salmon skin gelatin and trimmings-derived protein hydrolysates in vitro. The gelatin hydrolysate generated with Alcalase 2.4L and Flavourzyme 500L exhibited significantly higher (p < 0.001) insulin and GLP-1 secretory activity from pancreatic BRIN-BD11 and enter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
59
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(68 citation statements)
references
References 56 publications
6
59
0
3
Order By: Relevance
“…Thus, salmon frames were rich in protein, mainly from the remaining meat and minerals were mostly from bones. This was in agreement with Harnedy et al () who documented that salmon skin and trimmings derived during salmon filleting process, contained significant quantities of protein. Salmon frame showed higher ash content than Alaska pollock counterpart (14.99%) (Hou, Li, Zhao, Zhang, & Li, ).…”
Section: Resultssupporting
confidence: 92%
“…Thus, salmon frames were rich in protein, mainly from the remaining meat and minerals were mostly from bones. This was in agreement with Harnedy et al () who documented that salmon skin and trimmings derived during salmon filleting process, contained significant quantities of protein. Salmon frame showed higher ash content than Alaska pollock counterpart (14.99%) (Hou, Li, Zhao, Zhang, & Li, ).…”
Section: Resultssupporting
confidence: 92%
“…This was in line with their pronounced insulinotropic actions in vitro . The present findings compare favourably with results published recently with other fish hydrolysates (Harnedy et al ., ,b). For example, in the case of blue whiting ( Micromesistius poutassou ) a two‐fold higher dose of protein hydrolysate (100 mg mL −1 ) generated using Alcalase 2.4 L and Flavourzyme 500 L had a similar acute glucose‐lowering effect (22% AUC (0–120 min) reduction) following an OGTT in normal healthy mice (Harnedy et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Research into marine protein and its subsequent hydrolysates and isolated bioactive peptides targeting diabetes and its complications is limited. Nevertheless, some early studies have shown the beneficial effects of inhibiting dipeptidyl peptidase‐4 (DPP‐IV) (Huang et al ., ; Harnedy et al ., , ,b; Silaa et al ., ), and thus lowering glycated haemoglobin (HbA 1c ) in human volunteers with T2DM (Zhu et al ., ). The aims of the present study were firstly to investigate the in vitro insulinotropic and GLP‐1 stimulatory effects of a BPH, and secondly to investigate the effect of oral consumption of BPH on blood glucose control in healthy mice following an oral glucose challenge.…”
Section: Introductionmentioning
confidence: 99%
“…In Table 4, we have summarized examples of bioactive compounds recovered from animal and marine products processing wastes. [170][171][172]…”
Section: Bioactive Compounds From Animal Products Processing Wastementioning
confidence: 99%
“…Salmon nasal cartilage is a valuable source of bioactive proteoglycans reported for anti-angiogenic activity, relieving joint pain discomfort in elderly people and promoting wound healing [167][168][169]177]. Fish skin is also an important source of collagen that can be hydrolysed to bioactive peptides with multiple health benefits with antioxidant, anti-hypertensive, and anti-diabetic activities, as well as enhancing learning and memory [170][171][172].…”
Section: Fish and Shellfish Wastementioning
confidence: 99%